Male mouse skeletal muscle lacking HuR shows enhanced glucose disposal at a young age - Noland, Robert C.; Ghosh, Sujoy; Crisanto, Carlos J.; Aleman, Antonio; Chaney, McKenna K.; Chauhan, Maitri K.; Loftis, Layla G.; Goad, Ally C.; Rickman, Christin F.; Velasquez, Samuel E.; Warfel, Jaycob D. (Frontiers in Physiology, 2025)
IntroductionMetabolic flexibility is the ability of a system to switch between metabolic substrates. Human and murine skeletal muscle tissues and cells with decreased activity of the regulatory RNA-binding protein, human antigen R (HuR), have decreased capacity for fat oxidation, and thus decreased metabolic flexibility. In this study, we aimed to assess the preference for carbohydrates in mice lacking HuR in skeletal muscle.MethodsExperiments were performed on weight-matched control and HuR knockout mice of both sexes. Palmitate and pyruvate oxidation were performed in mouse muscle following the release of 14CO2. In vivo glucose and lipid uptake were assayed in mouse tissue following nonmetabolizable 3H-2-deoxyglucose or 14C-bromopalmitate injection. Transcriptomic analyses were performed in the skeletal muscle of all mice, followed by qPCR validation of select genes. Serum lactate and glucose levels were measured in mice via tail nick, and the muscle glycogen level was measured through colorimetric assay. Indirect calorimetry was used to measure respiratory exchange ratios.ResultsMale muscle-specific HuR knockout mice showed increased glucose uptake relative to controls, specifically in skeletal muscle, and have increased muscle glycogen content. These mice also displayed greater respiratory exchange ratios than controls. None of these differences were noted in females. Transcriptomics showed far more differences between male and female mice than between control and HuR knockout mice. However, differential gene expression between male and female mice was diminished by 50% following the removal of HuR. Male HuR knockout mouse skeletal muscle had increased glycolytic gene expression relative to controls but showed no difference relative to females of the same genotype. Both palmitate and pyruvate oxidation were decreased in the skeletal muscle of male HuR knockout mice relative to controls, and serum lactate levels were increased. No notable differences were seen in females between genotypes.DiscussionThe increase in the markers of glucose utilization with decreased HuR activity in male mice may indicate a switch toward glycolysis as compensation for decreased fat oxidation. These results continue to highlight a sex dependence on HuR as a driver of fat oxidation in mouse skeletal muscle while also indicating that muscle itself shows greater ambiguity between males and females following the removal of HuR.